How to acquire retain or renew knowledge - William Edridge (South African Medical Association, 2015)
When we teach and when we learn, guidelines, protocols, research papers and current information in general are a great assistance. They inform our debates and discussions. They assist us in steering away from the turbulence of medicolegal enquiry, rather to tread the path that is accepted and endorsed. But we should not forget that almost nothing is beyond challenge: that the inconsistencies that we cannot see trouble young minds; that it takes courage to accept their criticisms and to realise that we inhibit learning, stifle progress and prevent good logical care of patients by failing to observe what we see; and that when we sit with students or those who come to learn at our scanners or in our operating theatres, incomplete knowledge may hinder and not help.